Measurement of the t(t)over-bar production cross section in the tau plus jets channel using the ATLAS detector - Aad, G; Abajyan, T; Abbott, B; Abdallah, J; Khalek, SA; Abdelalim, A; Abdinov, O; Aben, R; Abi, B; Abolins, M; AbouZeid, O; Abramowicz, H; et al. (2013)
A measurement of the top quark pair production cross section in the final state with a hadronically decaying tau lepton and jets is presented. The analysis is based on proton-proton collision data recorded by the ATLAS experiment at the LHC, with a centre-of-mass energy of 7 TeV. The data sample corresponds to an integrated luminosity of 1. 67 fb-1. The cross section is measured to be σtt̄ = 194 ± 18 (stat.) ± 46 (syst.) pb and is in agreement with other measurements and with the Standard Model prediction. © 2013 CERN for the benefit of the ATLAS collaboration.